Musik Pengiring dalam Upacara Ngalaksa Masyarakat Rancakalong Sumedang - ELA YULAELIAH (Institut Seni Indonesia Yogyakarta, 2008)
Accompanying Music in Ngalaksa Ceremony at Rancakalong Community of Sumedang. This researchis intended to study the important role of music accompanying Ngalaksa ceremony held by the society of Rancakalong,Sumedang District, West Java. Although this ceremony is recently oriented to be a tourist destination, butits original function as a thanksgiving ceremony and original form of ceremony is still kept in accordance with thecustom inherited from generation. One thing that can not be separated from Ngalaksa ceremony is the Tarawangsamusic performance and Kecapi played for seven days and seven nights. By using Etnomusicological approach, it canbe known that the music within Ngalaksa ceremony plays a very important role for generating religious situationand for accompanying spontaneous dances.